A Nonlinear Strength Criterion of Frozen Saline Sandy Soil at High Pressures. (3rd August 2022) - Chang, Dan; Feng, Lizhen; Liu, Jiankun; Dai, Beibing
Abstract : The strength of frozen saline soil is influenced by various factors, such as confining pressure, salt content, and temperature. To investigate the influences of these factors on strength parameters, a series of triaxial tests were performed for frozen saline samples. According to the test results, as the mean principal stress increases, the failure strength increases firstly and then reaches a peak value, followed by a decreasing tendency. The pressure corresponding to ice melting is higher for frozen samples at a lower temperature. A strength function, which consists of cohesion and friction components, is developed in p ‐ q plane. Then, the relationships between temperature and strength parameters are given by fitting the test data. The envelope between those for the SMP and von Mises criteria is employed to describe the strength properties in π plane. By comparing the predicted data with test results, the developed strength criterion can well reproduce the strength variation of frozen sandy samples considering the effects of confining pressure, salt content, and temperature.